Externalities of vocational Education within the Context of managing development of vocational education and training institutors - Сергеєва, Л. М. (Pedagogy of Higher and Secondary Education, 2012)
Sergeeva L. Externalities of vocational Education within the Context of managing development of vocational education and training institutors. The article describes conditions for the development and functioning of the educational services sector within vocational education and training institutions; it defines key externalities of vocational education institutions as an open social system and analyzes factors for its institutionalization.